2011
DOI: 10.1021/jf202701b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Milled Wood Lignin (MWL) in Loblolly Pine Stem Wood, Residue, and Bark

Abstract: Milled wood lignin samples from Loblolly pine stem wood, forest residue, and bark were isolated and characterized by quantitative (13)C and (31)P nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FT-IR), and gel permeation chromatography (GPC) for molecular weight determination. Results from (13)C NMR show the stem wood and forest residue samples have similar functional group contents. However, the bark has fewer methoxyl groups, β-O-4 structures, dibenzodioxocin, and side chains than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 24 publications
(69 reference statements)
7
77
1
Order By: Relevance
“…The significant observation from the reported results is that the S-type compounds increase with an increase in the severity of the wet explosion conditions. This was found to contradict the previous observations made by studying the effect of steam explosion and wet oxidation separately on lignocellulosic biomass [30][31][32][33][34] since these studies indicated that S units after pretreatment are cleaved to produce more G units resulting in a reduction in the S/G ratio and an increase in the lignin surface condensation. However, from both the NMR and the GC-MS analysis, wet explosion pretreatment showed an increase in the S units and decrease of H and G, which could best be explained through a selective methoxylation of H and G lignins during the pretreatment.…”
Section: Lignin-derived Phenolic Compounds As Determined By Gc/mscontrasting
confidence: 70%
See 1 more Smart Citation
“…The significant observation from the reported results is that the S-type compounds increase with an increase in the severity of the wet explosion conditions. This was found to contradict the previous observations made by studying the effect of steam explosion and wet oxidation separately on lignocellulosic biomass [30][31][32][33][34] since these studies indicated that S units after pretreatment are cleaved to produce more G units resulting in a reduction in the S/G ratio and an increase in the lignin surface condensation. However, from both the NMR and the GC-MS analysis, wet explosion pretreatment showed an increase in the S units and decrease of H and G, which could best be explained through a selective methoxylation of H and G lignins during the pretreatment.…”
Section: Lignin-derived Phenolic Compounds As Determined By Gc/mscontrasting
confidence: 70%
“…2. Previous studies have been done for comparing the effect of various pretreatment methods on the loblolly pine lignin structure and are the basis for the discussions on chemical shifts for the 13 C NMR spectra used in this study [28][29][30]. The 13 C NMR spectra of raw biomass showed a typical softwood lignin comprising of G lignin, i.e., it largely comprised the expected prevailing G aromatic ring resonances together with characteristic methoxy (−OMe) group signals (δ C~5 5.8 ppm).…”
Section: One-dimensional 13 C Nuclear Magnetic Resonancementioning
confidence: 99%
“…Clearly, it can be seen that the aliphatic hydroxyl group was the dominant hydroxyl type in these three lignin samples. This finding was consistent with previous study for milled wood lignin (Huang et al 2011). Among them, L1 had the highest content of aliphatic hydroxyl groups, followed by L2, and finally L3.…”
Section: Lignin Structural Analysis Using Quantitative 31 P-nmrsupporting
confidence: 93%
“…Loblolly pine (P. taeda) has a total lignin content of 28%, and a H/G ratio of 0.01, i.e., guaiacyl units largely predominate over p-hydroxyphenyl units [95].…”
Section: Pinusmentioning
confidence: 99%
“…In Pinus taeda, bark lignin ranged from 32.9 to 43.5% [95,166]. It is mainly constituted by guaiacyl and p-hydroxyphenyl units, with reported H/G ratio values of 0.59 (the value for wood lignin is 0.01) [95] and 0.28 [166].…”
Section: Pinus Barksmentioning
confidence: 99%